The Moral Wager - Murray, Malcolm. author. aut Link
IX, 247 p.
Keywords: This book illuminates and sharpens moral theory, by analyzing the evolutionary dynamics of interpersonal relations in a variety of games. We discover that successful players in evolutionary games operate as if following this piece of normative advice: Don't do unto others without their consent. From this advice, some significant implications for moral theory follow. First, we cannot view morality as a categorical imperative. Secondly, we cannot hope to offer rational justification for adopting moral advice. This is where Glaucon and Adeimantus went astray: they wanted a proof of the benefits of morality in every single case. That is not possible. Moral constraint is a bad bet taken in and of itself. But there is some good news: moral constraint is a good bet when examined statistically.